UJI IMAGE UNIFORMITY PERANGKAT COMPUTED RADIOGRAPHY DENGAN METODE PENGOLAHAN CITRA DIGITAL - Arnefia Mei Yusnida; Suryono Suryono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Image uniformity on Computed Radiography (CR) indicates the ability of photostimulable phosphor that contained in the imaging plate (IP) in generating value gray level at all points on the same exposure treatment. Image uniformity determine the image quality on radiological examination to be able to obtain accurate diagnostic information. Determination of image uniformity can be achieved by digital image processing. In this study, image uniformity tests performed using imaging plate size 35 x 35 with ID plate 9103073519. Imaging plate was exposured at 80 kV tube voltage and currents and the time variation of 40 mAs, 50 mAs and 60 mAs. Furthermore searched pixel values in the region of interest (ROI) which has been determined. Data from the test image is processed with Matlab software. The average deviation of each ROI pixel generated by the test images ranged between 0.17% -1.03% of the overall average. This value is still within the tolerance limit of 10% set by the AAPM, so the tapes were tested said to be unsuitable for use. Keywords: image uniformity, imaging plate, digital image, region of interest, deviation